(untitled) (PERcursos Linguísticos, 2024)
ABSTRACT: This paper aims to draw on ecological thought and neurodiversity studies to approach their relationship with foreign languages. Based on the premise that the current moment (the climate catastrophe) evidences the modern framework, we aim to approach neurodiversity beyond the modern framework, questioning the homogenizing normativity that categorizes beings based on hierarchies. In this sense, when a thought without center or margins, i.e. the ecological thought, is brought into the discussion, the relationship with foreign languages can be viewed differently. We suggest, therefore, that if we observe the performance of executive functions in neurodivergent, bilingual, and non-white individuals, we can perceive that the use of a foreign language in linguistic practice can create an alternative environment where the conventional cognitive pattern ceases to be the central point. This foreign and strange space-time is, by its very nature, non-uniform and branched, allowing for the equalization of neurodivergent and neurotypical individuals. Thus, the present article seeks to contribute to foreign language teaching through the dialogue between ecological thought and neurodiversity studies. KEYWORDS: Neurodiversity. Ecological thought. Modernity. Foreign language.